Perbedaan Privasi Dan Rahasia Dalam Relasi: Studi Netnografi Vidio TikTok @Hezkieltimothee - Lisa Harmelina; Santi Delliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Differences in privacy and confidentiality exist from individuals or groups of individuals to protect their needs in personality. The purpose of this study is to analyze the perception of informants in the @Hezkiieltimothee regarding differences in privacy and confidentiality in comments from a netnographic study. Researchers used CPM, Netnography. Researchers used Analysis; comfortable living in a private relationship, choosing to live privately because they don't want their relationship to be seen by the public, private boundaries in relationships, namely five informants do not indulge in problems on social media, are always there for their partners, publish as necessary, one of the partners did not agree to live in a private relationship then one of them convinced. five informants chose their current partner because they believed their partner was much better than the previous one. informants accept the changes that occur because they are not excessive. Informants quarreled for less than 24 hours except Nadia.